Efektivitas Teks Persuasif dalam Strategi Komunikasi Pemasaran Digital di Platform TikTok - Siregar, Feby Yoana (Linguistik, Terjemahan, Sastra (LINGTERSA), 2025)
This study aims to describe the forms and strategies of persuasive sentences used in sales advertisements on the TikTok platform, focusing on the local account @TikLove.id. The background of this study is based on the importance of language as the main tool in digital marketing communication, especially in social media that demands speed, interactivity, and an emotional approach to the audience. The aim is to describe the forms and strategies of persuasive sentences they use in advertising content. Using a qualitative descriptive method, researchers collected data in the form of 12 advertising sentences described in terms of language form, communicative intent, and persuasive strategies applied. The results show that direct invitation sentences (imperatives) and exclamations (interjections) are most widely used. Strategies such as creating a sense of urgency, building emotional closeness, and adjusting to the lifestyle of the digital audience are key to attracting attention. The novelty of this study lies in its specific approach exploring persuasive language in short video content that is local, practical, and close to the daily lives of Indonesian people. This study not only adds insight into how language works on social media, but also provides a real picture of how small business actors utilize the right communication style to reach consumers. This research bridges the gap between linguistic studies and current digital marketing practices.